End of the political cycle of the Popular Front governments (Progressives) South American? - Da Silva, Luiz Fernando [UNESP]; Costa, Gisele C. [UNESP] (Univ Zulia, Consejo Desarrollo Cientifico & Humanistico, 2018)
The discontent of the workers and social strata more impoverished in Latin America in front of the neoliberal policies provoked the emergence of political forces that, in the direction of the workers' and popular movements, reconstituted the bourgeois-democratic order. Composed of social movements, parties of the left and fractions of Capital, governments in various South American countries emerged whose nature was the conciliation of classes. Favored by global economic growth between the beginning and the middle of the first decade of the twenty-first century, these governments promoted compensatory policies in countries such as Brazil, Venezuela, Argentina, Bolivia, and Ecuador, which at first allowed the basic needs of the poorest sectors, a fact that created for such social forces a great social and political base. However, with the worsening of the international economic crisis and the application of austerity policies by the progressive governments, elected with an antineo-liberal discourse, a triple economic, social and political crisis has opened up in some of these countries, in which such governments have lost a significant part of their support base. In this sense, the objective of this paper is to present the trajectory, political nature and determinations that provoked the first but severe signs of weakening the so-called progressive governments of South America.
Keywords: South America; governments; economic; political and social crisis